Genetic and biochemical evidence for the lack of significant hydrolysis of soman by a Flavobacterium parathion hydrolase. - Pogell, B M (1991)
Pure recombinant Flavobacterium parathion hydrolase (an organophosphorus acid anhydrase) from Streptomyces lividans was found to hydrolyze the toxic nerve agent soman at only 0.1% of the rate observed with parathion as substrate. Studies with wild-type and recombinant strains of S. lividans support the lack of significant soman breakdown by the hydrolase and also indicate the presence in S. lividans of other significant hydrolytic enzymatic activity towards soman.